Analysis of Physical and Technical Performance of Substitute Players in Professional Soccer - Lorenzo-Martínez, Miguel; Padrón-Cabo, Alexis; Rey, Ezequiel; Memmert, Daniel (Research quarterly for exercise and sport, 2021)
Current soccer scientific literature is scarce with regard to examining the technical performance of substitute players. Purpose: This study aimed to analyze the physical and technical performance of substitute players versus those who completed the entire match or were replaced and also examine the performance of substitutes across different playing positions. Method: The sample was composed of 6,631 match observations from 431 professional soccer players competing in the German Bundesliga during the season 2018-2019. These observations were divided into three groups: entire match (n = 3,807), replaced (n = 1,412), and substitutes (n = 1,412). Linear mixed models were adjusted to compare the performance of the three groups independently of playing position and separately for each position (central defenders, fullbacks, central midfielders, wide midfielders, and attackers). Results: Substitute players showed higher total distance covered (effect sizes [ES]: 0.99-1.06), number of sprints (ES: 0.60-0.64), and number of fast runs (ES: 0.83-0.91) relative to playing time than replaced and entire match players. The differences in technical performance between groups varied according to playing position. Substitute central defenders showed less possession (ES: 0.39-0.41), touches (ES: 0.47-0.57), and passes (ES: 0.54-0.59) but higher defensive performance (ES: 0.51-0.54) than replaced and entire match players. Substitutes in midfield and attack positions displayed more possession (ES: 0.22-0.47), touches (ES: 0.27-0.37), and shots (ES: 0.22-0.28) than replaced and entire match players. Conclusion: This study has shown that substitutes are able to improve the performance of the players who completed the entire match or were replaced in both physical and some technical variables depending on playing position.